Estudo do índice de qualidade educacional (IQE) e seu efeito nos resultados educacionais e nas transferências da parcela discricionária da cota parte do ICMS nos municípios do Ceará - Batista, José Marques (2020)
Brazil is a country with educational and public health deficits that generate enormous waste of human capital and poor economic performance, since these aspects induce a substantial part of the population to a vicious cycle of low levels of productivity and income, the well-known “trap poverty ”. This situation occurs in poor regions, in which there is an asymmetrical distribution of income and a precarious supply of public services in the area of Health and Education, restricting the possibilities of people in the lower classes to explore their individual capacities. In view of this scenario, the present research aimed to analyze the Educational Quality Index (EQI) and verify the effect both on educational results and on transfers from the discretionary part of the ICMS quota in 184 municipalities of Ceará. To this end, the mechanisms of intergovernmental transfers present in the Brazilian Constitution of 1988 were addressed, as well as the logic involved in the EQI proposal, the debate between federalism and constitutional transfers and the effect of EQI in increasing educational results in Ceará, in addition to secondary data from Ceará’s Economic Research and Strategy Institute (IPECE), the Treasury Secretariat of the state of Ceará (SEFAZ), the Basic Education Assessment System (SAEB) and Ceará’s Permanent Basic Education Assessment System ( SPAECE). Descriptive and inferential statistical analyzes were carried out in order to describe, compare and highlight the groups of municipalities that behaved in a different way, that is, those that most evolved in their educational and financial indicators through the transfer of the ICMS’ share between 2009 and 2019. The findings confirmed the efficiency of the IQE in the educational evaluation policy and in the intergovernmental transfer policy. Throughout the policy, smaller, poorer municipalities were able to allocate more resources through IQE.